2010
DOI: 10.1088/0004-6256/140/6/1965
|View full text |Cite
|
Sign up to set email alerts
|

A Radio Perspective on the Wet Merger Remnant NGC 34

Abstract: We present Very Large Array observations of the neutral hydrogen and radio continuum of NGC 34 (= NGC 17 = Mrk 938). This object is an ideal candidate for studying the fate of gas in mergers, since, as shown by an optical study done by Schweizer & Seitzer, it is a gas-rich ("wet") merger remnant of two disk galaxies of unequal mass hosting a strong central starburst and a weak active galactic nucleus (AGN). We detect H i emission from both tidal tails and from nearby galaxies, suggesting that NGC 34 is actuall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…This value lies between the values estimated by Vega et al (2008) of 21 and 151 M ⊙ yr −1 based on SED fitting for star formation in the last 10 Myr and averaged over the entire burst, respectively. Also, our derived SFR is similar to the 64 M ⊙ yr −1 obtained from 1.4‐GHz observations (Fernández et al 2010).…”
Section: Starburst Activitysupporting
confidence: 86%
See 1 more Smart Citation
“…This value lies between the values estimated by Vega et al (2008) of 21 and 151 M ⊙ yr −1 based on SED fitting for star formation in the last 10 Myr and averaged over the entire burst, respectively. Also, our derived SFR is similar to the 64 M ⊙ yr −1 obtained from 1.4‐GHz observations (Fernández et al 2010).…”
Section: Starburst Activitysupporting
confidence: 86%
“…These revealed that the mid‐IR emission in this system originates in the central ∼800 pc (Miles et al 1996), but it actually dominates in a region of ∼400 pc (see discussion in ). Fernández et al (2010) detected H i emission from both tidal tails and from nearby galaxies, suggesting that Mrk 938 is part of a gas‐rich group of galaxies. They also found a hint of emission between Mrk 938 and NGC 35, the largest companion lying at a projected distance of 131 kpc, and suggested that they might have recently interacted.…”
Section: Introductionmentioning
confidence: 99%
“…For NGC 34, Fernández et al (2010) calculated the SFR from radio luminosity and found a value of 64 M yr −1 (in a 3 × 2 beam), in agreement with SFR∼50 M yr −1 derived by Prouton et al (2004) from the FIR luminosity for similar beam. For NGC 1614, Alonso-Herrero et al (2001) found SFR=52 M yr −1 from integrated FIR luminosity (in a 45 × 250 beam) and assuming that 70% of this star formation occurs in the nucleus, they predict a nuclear SFR of 36 M yr −1 .…”
Section: Emission Gassupporting
confidence: 77%
“…In addition to this structure, we find an extended Paα emission-line region along the southern spiral arm which is located outside the field of view of the HST /NICMOS observation. This galaxy, hosting a strong starburst and a weak AGN, as evidenced by its optical, infrared, radio, and X-ray properties, is known as a remnant of unequal gas-rich merger (e.g., Fernández et al 2010;Schweizer & Seitzer 2007). It is an S0/a (HyperLeda) and classified as a Seyfert 2 by a long-slit spectroscopic study (Veilleux et al 1995).…”
Section: Paα Fluxmentioning
confidence: 99%